The memory of a forgotten exile: Eugen Lozovan and the intellectual dissent - Mircea-Cristian Ghenghea (Revista Română pentru Studii Baltice şi Nordice, 2019)
Thirty years after the dissolution of the totalitarian regime in Romania, due to various reasons, most of the names of those who were forced to leave the country and choose the exile remained practically unknown to the general public, in spite of the fact that a good part of them contributed to the maintenance of a certain Romanian anti-communist resistance worldwide. One of these names is Eugen Lozovan, a distinguished scholar and a voice of the Romanian intellectual dissent from the end of the 1950s until the 1980s. Since the importance of his work as a linguist, historian, and philologist began to be widely acknowledged in his native country within the last decades, it seems of equal importance to consider his opposition towards the communist regime which controlled Romania from 1947 until 1989. He permanently took a stance and expressed his opinions through various texts published in Romanian periodicals from Western Europe, which necessarily add to the memory of the general intellectual anti-communist resistance. This is one of the reasons why in the present text we try to underline his figure and his contributions published in exile in order to better understand the significance and the impact they had for the Romanian intellectual dissent.